Luminescence Quenching of Eu(III) Carboxylates by Cu(II) in a Composite Polymer Xerogel Film - Barja, Beatriz Carmen (2006)
Three Eu(III) luminescent compounds were separately entrapped in a xerogel porous silica matrix and finely ground particles of it were deposited on a glass support with polyvinylacetate (PVAc) as a binder to build a thin film sensor. These 3 devices were immersed in aqueous solutions of Cu(II) and the content of this metal was evaluated by emissionquenching experiments. The sensor containing the highly luminescent antenna chelate of diethylenetriaminepentaacetic acid (dtpa) sensitized with Coumarin120 rendered the largest Stern-Volmer constant (KSV 5 1.49 3 104 M21 ), showing no leaching of the Eu(III) complex to the aqueous solution and a reproducible value of the luminescence ratio between water and Cu(II) solution. The in situ sensor we developed can measure the concentration of Cu(II) in aqueous media down to the ppm level by emission-quenching experiments. This methodology permits a simple calibration of the sensor and an easy to use reusable device.